A Comparative Workforce Study of Midwives Practicing in the State of Texas. (8th June 2018) - Burpo, Rebecca H.; Nodine, Priscilla M.; Hastings‐Tolsma, Marie; Brucker, Mary C.; Griggs, Jackie; Wilcox, Sarah; Camune, Barbara D.; Callahan, Tiffany
Abstract : Introduction: Access to quality care is a problem in Texas, an ethnically diverse state with large birth numbers. The state has over 300 areas designated as medically underserved, and a severe lack of obstetricians and midwives. Minimal data exist on midwifery's contribution, and no known study compares the work environment and clinical practice of the 2 state‐recognized midwifery paths, licensed midwives (LMs) and certified nurse‐midwives (CNMs). The purpose of this study was to determine the differences in practice by CNMs and LMs, the latter of whom are generally certified professional midwives. The specific aims were to 1) describe the differences in demographic and employment characteristics of CNMs and LMs, 2) identify the geographic areas and population groups served by CNMs and LMs, and 3) compare the nature and scope of CNM and LM clinical practices. Methods: Online parallel surveys of Texas LMs and CNMs were conducted in December 2015 and January 2016. The REDCap data management system housed the 123‐ and 125‐item surveys for LMs and CNMs, respectively, addressing demographics, populations served, and clinical practice. A comparative statistical analysis, using Fisher's exact test, Pearson's chi‐squared test, and Independent Samples t‐tests, was performed. Results: The survey response rates of LMs and CNMs were 35.4% (n = 75) and 31.9% (n = 143), respectively. Differences in demographics, employment status, workload, scope of practice, risk assessment, time‐based care management, and technology use were observed. Discussion: Findings represent the first attempt to describe the Texas midwifery workforce. In a large state with health care provider shortages, this step is pivotal in addressing strategies for providing services for women and infants. This groundwork can provide the foundation for including midwifery in a state health plan.